Monoterpenes: Essential Oil Components with Valuable Features - Dehsheikh, Anahita B.; Sourestani, Mohammad Mahmoodi; Dehsheikh, Paria Boveiri; Mottaghipisheh, Javad; Vitalini, Sara; Iriti, Marcello (Mini Reviews in Medicinal Chemistry, 2020)
Medicinal plants have a wide range of secondary metabolites including monoterpene. These volatile compounds are the main components of essential oils, belonging to the isoprenoid group and possessing valuable features for plants and humans. This review provides comprehensive information on chemical structures and classification of monoterpenes. It describes their biosynthesis pathways and introduces plant families and species rich in noteworthy monoterpenes. Bio-activities, pharmacological and pesticide effects as well as their mechanism of action are reported. Applications of these compounds in various industries are also included.
Keywords: bioherbicides